Organ Donation at the End of Life: Experiences From the 3 Wishes Project. (April 2021) - Takaoka, Alyson; Honarmand, Kimia; Vanstone, Meredith; Tam, Benjamin; Smith, Orla M.; Baker, Andrew; LeBlanc, Allana; Swinton, Marilyn; Neville, Thanh H.; Clarke, France J.; Hancock, Jennifer; McMullen, Sarah; et al.
Purpose: The 3 Wishes Project (3WP) promotes holistic end-of-life care in the intensive care unit (ICU) to honor dying patients, support families, and encourage clinician compassion. Organ donation is a wish that is sometimes made by, or on behalf of, critically ill patients. Our objective was to describe the interface between the 3WP and organ donation as experienced by families, clinicians, and organ donation coordinators. Methods: In a multicenter evaluation of the 3WP in 4 Canadian ICUs, we conducted a thematic analysis of transcripts from interviews and focus groups with clinicians, organ donation coordinators, and families of dying or died patients for whom donation was considered. Results: We analyzed transcripts from 26 interviews and 2 focus groups with 18 family members, 17 clinicians, and 6 organ donation coordinators. The central theme describes the mutual goals of the 3WP and organ donation—emphasizing personhood and agency across the temporal continuum of care. During family decision-making, conversations encouraged by the 3WP can facilitate preliminary discussions about donation. During preparation for donation, memory-making activities supported by the 3WP redirect focus toward personhood. During postmortem family care, the 3WP supports families, including when donation is unsuccessful, and highlights aspirational pursuits of donation while encouraging reflections on other fulfilled wishes. Conclusions: Organ donation and the 3WP provide complementary opportunities to engage in value-based conversations during the dying process. The shared values of these programs may help to incorporate organ donation and death into a person's life narrative and incorporate new life into a person's death narrative.